Penerapan Model Problem Based Learning dalam Meningkatkan Hasil Belajar Peserta Didik Kelas IV UPTD SD Negeri 11 Kampung Baru - Hudri, Hudri (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
The learning process that has been taking place so far has mainly been focused on transferring knowledge from the teacher to the students, without ensuring whether the students truly understand the material. Additionally, students have difficulty summarizing the material as they simply listen without paying full attention or retaining the information given. As a result, the lessons taught by the teacher cannot be recalled later. The teacher often resorts to lecturing, which causes students to be less engaged with the content. This study aims to examine the extent to which the use of the Problem-Based Learning model can improve students' learning outcomes in the material of the noble example of Asmaul Husna in the Islamic Religious Education (PAI) subject. The method used in this study is Classroom Action Research (CAR). The results of the research show that the application of the Problem-Based Learning model in the PAI subject significantly aids students' understanding, especially regarding the noble example of Asmaul Husna. This model encourages students to be more active and makes it easier for them to comprehend the material. The learning process becomes enjoyable and less monotonous. The Classroom Action Research using the Problem-Based Learning model has produced positive results.